2020
DOI: 10.1038/s41598-020-60119-x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave radiation-induced grafting of 2-methacryloyloxyethyl trimethyl ammonium chloride onto lentil extract (LE-g-DMC) as an emerging high-performance plant-based grafted coagulant

Abstract: The importance of graft copolymerization in the field of polymer science is analogous to the importance of alloying in the field of metals. This is attribute to the ability of the grafting method to regulate the properties of polymer 'tailor-made' according to specific needs. This paper described a novel plantbased coagulant, LE-g-DMC that synthesized through grafting of 2-methacryloyloxyethyl trimethyl ammonium chloride (DMC) onto the backbone of the lentil extract. The grafting process was optimized through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
(26 reference statements)
8
15
0
Order By: Relevance
“…In the FTIR analysis, observed peaks encompassed various functional groups, including, but not restricted to, C-O-C (1098 cm -1 , 1196 cm -1 , 1262 cm -1 , 1284 cm -1 ), C=O (1720 cm -1 , 1756 cm -1 ), S=O (1357 cm -1 ), C-H (3010 cm -1 ), C-SO2-N (1147 cm -1 , 1329 cm -1 ), and C-F (748 cm -1 ) in the LiTFSI and LiTFSI-ES system. These spectral features aligned closely with the wavenumber data reported in prior investigations [43][44][45][46][47][48][49], reinforcing the consistency and reliability of the spectral assignments made in this study.…”
Section: Resultssupporting
confidence: 89%
“…In the FTIR analysis, observed peaks encompassed various functional groups, including, but not restricted to, C-O-C (1098 cm -1 , 1196 cm -1 , 1262 cm -1 , 1284 cm -1 ), C=O (1720 cm -1 , 1756 cm -1 ), S=O (1357 cm -1 ), C-H (3010 cm -1 ), C-SO2-N (1147 cm -1 , 1329 cm -1 ), and C-F (748 cm -1 ) in the LiTFSI and LiTFSI-ES system. These spectral features aligned closely with the wavenumber data reported in prior investigations [43][44][45][46][47][48][49], reinforcing the consistency and reliability of the spectral assignments made in this study.…”
Section: Resultssupporting
confidence: 89%
“…Klimkevicius et al reported that the ζ-potential of titania nanoparticles changed from −60 to 60 mV after poly­(METAC) coating . Poly­(METAC) was modified to lentil extracts as plant-based conjugated materials . The original negative charges of the lentil extracts (−5.91 mV) changed to 15.08 mV after modification with cationic poly­(METAC).…”
Section: Resultsmentioning
confidence: 99%
“…54 Poly(METAC) was modified to lentil extracts as plant-based conjugated materials. 55 The original negative charges of the lentil extracts (−5.91 mV) changed to 15.08 mV after modification with cationic poly(METAC). The ζ-potentials of the PVA/3D_25 wt % and PVA/3D_50 wt % films were 1.4 ± 1.5 and 9.4 ± 0.8 mV, respectively.…”
Section: Acsmentioning
confidence: 99%
“…WCA tests showed that PU was hydrophobic, judging by its WCA of 93° (see Figure 5 ) [ 46 , 47 ]. After the immobilization, WCA increased to 102° because of the presence of a more hydrophobic Br– containing initiator [ 43 ].…”
Section: Resultsmentioning
confidence: 99%